Respostas

2013-07-15T19:29:47-03:00
A) ñ tem conta, c olha lá só o gráfico => função constante
 
b) f(x) = 3x - 2 p/ x = 0, -1, 1

   f(x) = 3* 0 - 2 = -2
   f(x) = 3*(-1) - 2 = - 5
   f(x) = 3 * 1 - 2 = 1

=> função crescente

c) f(x) = 2x  p/ x = 0, 1 , -1, 2
   
   f(x) =  2 * 0 = 0
   f(x) = 2 * 1 = 2
   f(x) = 2* (-1) = -2
   f(x) = 2 * 2 = 4
=> função crescente

d) f(x) = 2x + 1  p/ x = -1, 0, 1, 2
   
    f(x) = 2* (-1) + 1 = - 1
    f(x) = 2* 0 + 1 = 1
    f(x) = 2* 1 + 1 = 3
    f(x) = 2* 2 + 1 = 5

=> função crescente
2 5 2